A Metallurgical Evaluation Of A Heavy Mineral Sand Deposit Based On Stratigraphic Unit Classifications - L. I. Boshoff; S. Gracie (The Southern African Institute of Mining and Metallurgy, 2007)
This paper discusses pilot and laboratory-scale metallurgical test work conducted on bulk samples from a low grade heavy mineral deposit and provides an overview of basic practical metallurgical techniques applied to ascertain the suitability of existing production plants to process material from this orebody. Previous investigations have shown this specific orebody to be more challenging in terms of mineral beneficiation as it has a high gangue mineral content. Test work was conducted on targeted stratigraphic units based on lithology and assay results to enable identification of the stratigraphic units portraying quality issues. Unit specific metallurgical pilot work has never been conducted on any of the RBM orebodies and is a new field currently being explored. During this investigation focus was placed on potential quality and yield issues for ilmenite product, with particular reference to CaO quality. A basic evaluation of zircon and rutile separability was also conducted. The test work was conducted using a comparative baseline methodology with metallurgical test work methods specifically aiming at mimicking the existing production plant as closely as possible. This enabled not only the likely metallurgical performance to be assessed but also indicated whether current plant design would be suitable to process the low grade ore types into products of acceptable quality at acceptable yields. The methods and findings discussed in this paper indicate that although there is considerable variation between different units, a blended feed can be successfully processed. With unit specific metallurgical data applied to the existing geological block model, expected yields and recoveries using current plant designs could be predicted.